FAINT BLUE STARS IN THE REGION NEAR THE SOUTH GALACTIC POLE - LUYTEN, WJ; HARO, G (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1967)
We present a catalogue of 8746 faint blue stars selected from 49 regions near the South Galactic Pole taken with the Palomar 48-inch Schmidt camera. The photographic material had 3 exposures through different filters to obtain UBV images. The catalogue is
BOL OBS TONAN TACUB
Keywords: FAINT, BLUE STARS, REGION NEAR, SOUTH, GALACTIC POLE; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; GALAXIAS